2013
DOI: 10.1371/journal.pone.0070655
|View full text |Cite
|
Sign up to set email alerts
|

MTB-3, a Microtubule Plus-End Tracking Protein (+TIP) of Neurospora crassa

Abstract: The microtubule (MT) “plus end” constitutes the platform for the accumulation of a structurally and functionally diverse group of proteins, collectively called “MT plus-end tracking proteins” (+TIPs). +TIPs control MT dynamics and link MTs to diverse sub-cellular structures. Neurospora crassa MicroTubule Binding protein-3 (MTB-3) is the homolog of yeast EB1, a highly conserved +TIP. To address the function of MTB-3, we examined strains with mtb-3 deletions, and we tagged MTB-3 with GFP to assess its dynamic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Consistent with the phenotypic changes of ΔFgEB1, the MAL3 deletion mutants of S. pombe produces branched and curved cells instead of the typical cylindrical shape of wild‐type cells (Beinhauer et al ., ). However, in filamentous fungus N. crassa , EB1 mutants only exhibited slightly reduced linear growth and increased conidiation, but did not show an obvious change in hyphal morphology in comparison with the wild type (Mouriño‐Pérez et al ., ). These studies indicate functions of EB1 homologs are species‐specific in different fungal species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with the phenotypic changes of ΔFgEB1, the MAL3 deletion mutants of S. pombe produces branched and curved cells instead of the typical cylindrical shape of wild‐type cells (Beinhauer et al ., ). However, in filamentous fungus N. crassa , EB1 mutants only exhibited slightly reduced linear growth and increased conidiation, but did not show an obvious change in hyphal morphology in comparison with the wild type (Mouriño‐Pérez et al ., ). These studies indicate functions of EB1 homologs are species‐specific in different fungal species.…”
Section: Discussionmentioning
confidence: 97%
“…In Saccharomyces cerevisiae, the EB1 ortholog Bim1 combining with Kar9 and Stu2 is involved not only in microtubule modulation in cytoplasm but also in the accurate positioning and elongation of spindle in anaphase (Miller et al, 2000;Meednu et al, 2008;Zimniak et al, 2009). However, the deletion of MTB-3 (encoding EB1) was found to slightly affect overall growth and morphological phenotypes of Neurospora crassa, although the mutant showed decreased polymerization and depolymerization rates of microtubule (Mouriño-P erez et al, 2013), indicating that the functions of EB1 in filamentous fungi might be different from those in the yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…Lis1, an MT plus-end-binding protein, is involved in the regulation of the dynein/dynactin complex in humans 75 . In N. crassa , two paralogues of Lis1—LIS1-1 and LIS1-2—were identified in the hyphal apical dome as short filaments or comet-like structures decorating the terminal plus-ends of the MTs 76 , similar to the distribution of the MT plus-end-binding protein MTB-3, a homologue of EB1 77 . LIS1-1 localization was found to be dependent on the minus-end-directed MT-associated motor dynein and dynactin (p150Glued) 76, 78 .…”
Section: Of Filaments and Nanomotors: Connecting Exocytosis And Endocmentioning
confidence: 94%
“…It was shown that a MT plus-end tracking protein (ϩTIP), an EB1 orthologue, accumulates at the tip and moves in a retrograde manner. Also, bleaching experiments suggested MT polymerization starting from the tip (133,134). Whether there are MTOCs at septa is still unsolved.…”
Section: The Fungal Cytoskeleton the Microtubule Cytoskeletonmentioning
confidence: 99%